2009
DOI: 10.1103/physreve.80.031602
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of bcc metals in phase-field-crystal models

Abstract: We examine the influence of different forms of the free-energy functionals used in the phase-field-crystal ͑PFC͒ model, and compare them with the second-order density-functional theory ͑DFT͒ of freezing, by using bcc iron as an example case. We show that there are large differences between the PFC and the DFT and it is difficult to obtain reasonable parameters for existing PFC models directly from the DFT. Therefore, we propose a way of expanding the correlation function in terms of gradients that allows us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
274
1
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(300 citation statements)
references
References 22 publications
16
274
1
9
Order By: Relevance
“…Consider Eq. (20) in the moving reference frame with the origin at the front invading unstable phase. Then, in Eq.…”
Section: Selection Of the Lattice Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…Consider Eq. (20) in the moving reference frame with the origin at the front invading unstable phase. Then, in Eq.…”
Section: Selection Of the Lattice Parametermentioning
confidence: 99%
“…It can be related to other continuum fields theories such as classical density-functional theory 8,9 and the atomic density function theory 10 . The PFC-model may also be considered as a conserved version of the Swift-Hohenberg equation and provides an efficient method for simulating liquid-solid transitions 11,12 , colloidal solidification 13 , dislocation motion and plasticity 14,15 , glass formation 16 , epitaxial growth 6,17 , grain boundary premelting 18 , surface reconstructions 19 , and grain boundary energies 20 .…”
Section: Introductionmentioning
confidence: 99%
“…With suitable choices of parameters for Fe (see Ref. 44), this model has been shown to predict reasonable values of solid-liquid interfacial energy 44,54 and GB energies 46 , despite the uncontrolled truncation of many other sets of reciprocal lattice vectors. It has also proven capable of reproducing a subtle dislocation-pairing GB structural transition at high homologous temperatures 23 , previously evidenced in a 2D PFC study of GB premelting 29 , and also observed in MD simulations 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we investigate GB premelting and shearing and their relationship using the PFC method [40][41][42][43][44][45][46] . We use the simplest PFC model 40,41 with the same freeenergy function as the Swift-Hohenberg model of pattern formation 47 , which favors hexagonal and bcc ordering in two and three dimensions (2D and 3D), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses are mainly limited to visual comparisons and relative energetics. Often, it is stated that the PFC-computed energies are not quantitatively comparable to molecular methods but that they follow similar trends as a function of some structural parameter, for instance grain boundary orientation 26,27 . However, to capture the structure, properties, and stress-driven thermally-activated phenomena that control kinetics requires accurate absolute energies.…”
Section: Introductionmentioning
confidence: 99%